MDS codec evaluation based on perceptual sound attributes - Herrera Martínez, Marcelo; Gómez, Edwar Jacinto; Vivas G., Edilberto Carlos (Visión electrónica, 2014)
The present paper deals with the subjective evaluation of audio coding technologies using the “Similarity Rating” psychometric method. Compressed audio excerpts are presented to a group of experienced listeners by pairs of stimuli. Each pair represents a different type of distortion, with compression included. These types of distortion correspond to three psychoacoustic attributes, sharpness, roughness, and fluctuation strength. Listener’s task is to evaluate the degree of similarity between the pairs. The final output is the localization of each measured codec in this psychoacoustic space. Multidimensional scaling is the statistic technique, belonging to Multivariate Statistical methods, which allows processing the results obtained from this method.